2014
DOI: 10.1371/journal.pone.0112430
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing of the World’s Oldest People

Abstract: Supercentenarians (110 years or older) are the world’s oldest people. Seventy four are alive worldwide, with twenty two in the United States. We performed whole-genome sequencing on 17 supercentenarians to explore the genetic basis underlying extreme human longevity. We found no significant evidence of enrichment for a single rare protein-altering variant or for a gene harboring different rare protein altering variants in supercentenarian compared to control genomes. We followed up on the gene most enriched fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 56 publications
(69 reference statements)
1
38
0
2
Order By: Relevance
“…Moreover, there was no decline in the frequency of disease-associated genetic variants carried by centenarians as compared to the general population [7]. In addition, A GWAS study of a small sample of the world’s oldest people (17 people over 110 years, 13 of them females) concluded that there is no evidence for enrichment of genetic variants in female Caucasian supercentenarians compared to controls [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there was no decline in the frequency of disease-associated genetic variants carried by centenarians as compared to the general population [7]. In addition, A GWAS study of a small sample of the world’s oldest people (17 people over 110 years, 13 of them females) concluded that there is no evidence for enrichment of genetic variants in female Caucasian supercentenarians compared to controls [8]. …”
Section: Introductionmentioning
confidence: 99%
“…[83][84][85] However, more variants that decrease gene function in the Teashirt Zinc Finger Homeobox 3 (TSHZ3) were observed in Centenarian and supercentenarian genomes (~110 years) than control genomes. 61 Considering these studies, we found that supercentenarians genomes did not contain an increased number of functional SIGLEC alleles in comparison to controls. Although the CD33 protective allele (also known as CD33m) helps reduce cognitive decline and Alzheimer's disease, the frequency of the variant was not significantly different between supercentenarian and control genomes which supports the conclusion that CD33rSIGLECs are not involved in regulating PRLS, but instead contribute to the regulation of reproductive lifespan.…”
Section: F I G U R E 3 Correlation Of Cd33rsiglec Genes With Maximummentioning
confidence: 77%
“…Additionally, variation in transcriptional profiles with aging was reported between mouse strains from diverse genetic backgrounds [98], signifying the importance of the genome in determining transcriptional regulation with age. Genetic factors are also thought to underlie increased longevity in supercentenarians [99,100] and may contribute to age-related epigenetic drift [101]. Therefore, population differences in methylation early in life, in addition to genetic diversity may be associated with the variability in development of age-related neuropathologies, predisposition, and severity observed between individuals.…”
Section: Enhancer Age-dmrs Are Related To Age-degsmentioning
confidence: 99%